(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
As a result of research it is defined that the condition of the upper basin of the Tysa river is become worse. Felled areas, overgrazing, disorderly recreation, quarries are the main negative factors of that. It is found that the most of todays wood-cutting areas are not artificially afforested for the last 10-15 years being in different stages of succesion from gramineous to dumetosus. Present state and basic factors of transformation of high mountain’s plant cover and meadow vegetation of a forest belt are characterized. It is found that the present structure of ecosystems under different economic use and of areas with natural vegetation can not afford balanced drainage.